If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 + 3x) * 2 = 48 Reorder the terms for easier multiplication: 2(6 + 3x) = 48 (6 * 2 + 3x * 2) = 48 (12 + 6x) = 48 Solving 12 + 6x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 6x = 48 + -12 Combine like terms: 12 + -12 = 0 0 + 6x = 48 + -12 6x = 48 + -12 Combine like terms: 48 + -12 = 36 6x = 36 Divide each side by '6'. x = 6 Simplifying x = 6
| 32+x=74-2x | | (4+2x)5=70 | | 16-2x=30-4x | | (4x-2)3=30 | | 1790=0.04x | | 2x/5x= | | 52=r*26 | | 2(5x+14)=33 | | -8(t-2)-(t+4)=9 | | 2x=7x-25 | | 3x=5x-1 | | 1.9=0.05x-98.40 | | 10-0.25(x+4)=0 | | 8x+15=5x | | 2002=0.05x-98.40 | | n=-98.40+0.05x | | 01x+32=85 | | x^2-5x-14=-10 | | y^2+3y-10=10 | | 4w(4w-3)=1-12w | | 7x-12=x+36 | | 35=-5t^2+10t+75 | | y^2-10y-8x+1=0 | | 6(x+.5)=x+8 | | 123+56=347 | | 9n-21=60 | | 8+6(2x-1)= | | 14X+13X+10X=2400000 | | 5x+3y=0 | | 5abc*5abc*5abc= | | 9(4x-8)-35x=3 | | 27-4x=2x+15 |